Hydrodynamic Cavitation in Shockwave-Power-Reactor-Assisted Biodiesel Production in Continuous from Soybean and Waste Cooking Oil - James R. Vera-Rozo; Edison A. Caicedo-Peñaranda; José M. Riesco-Avila (Energies)
The transesterification process for biodiesel production is constrained by high thermal input, prolonged residence time, and intensive mechanical agitation. This study investigates process intensification via hydrodynamic cavitation using a custom-built Shockwave Power Reactor (SPR), enabling continuous biodiesel synthesis from soybean and used cooking oils. A statistically designed experimental matrix was applied to evaluate the reactor’s transient–stable thermal regime and the influence of operational parameters: rotor speed (1700–3415 rpm), volumetric flow rate (60–105 mL/min), methanol-to-oil molar ratio (6:1 to 12:1), and alkali catalyst type (NaOH or KOH). For benchmarking, conventional alkaline transesterification was optimized. The FAME yields from the SPR system exceeded 96.5% and complied with EN14103 standards. Specific energy analysis showed that cavitation-enhanced transesterification reduced energy consumption and peak temperature compared to traditional methods. The SPR’s capacity to induce high shear and localized turbulence under controlled cavitation offers a promising pathway for low-energy, scalable biodiesel production.